2016
DOI: 10.1177/0149206316648384
|View full text |Cite
|
Sign up to set email alerts
|

Financially Linked Independent Directors and Bankruptcy Reemergence: The Role of Director Effort

Abstract: This study examines if the effort of financially linked independent (FLI) directors enable firms to reemerge from bankruptcy, a major organizational crisis. Using a sample of 307 bankrupt U.S. firms with instrumental variables regression methodology, I find that the efforts of these directors are critical for firm reemergence. FLI directors’ efforts increase the likelihood of reemergence as well as improve access to financial resources. In contrast, I do not find any evidence that non-FLI directors’ efforts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 101 publications
2
16
0
Order By: Relevance
“…Campello et al (2018) find that firms with a large percentage of their workforce in unions experience longer proceedings in bankruptcy court, with more bankruptcy emergences and subsequent refillings. Finally, Arora (2018) finds that the effort of financially linked independent directors increases the likelihood of emergence as well as improved access to financial resources.…”
Section: Extant Literaturementioning
confidence: 99%
“…Campello et al (2018) find that firms with a large percentage of their workforce in unions experience longer proceedings in bankruptcy court, with more bankruptcy emergences and subsequent refillings. Finally, Arora (2018) finds that the effort of financially linked independent directors increases the likelihood of emergence as well as improved access to financial resources.…”
Section: Extant Literaturementioning
confidence: 99%
“…We control for board size as prior research has shown it to be critical to firm performance, including social performance and external legitimacy (Arora, 2018). We similarly control for the proportion of independent directors.…”
Section: Board Size and Independencementioning
confidence: 99%
“…When a firm faces a takeover threat, AODs are more likely than IODs to stay with the firm (Daily & Dalton, 1994) and side with incumbent firm executives, thereby deriving higher premium offers (Bange & Mazzeo, 2004;Schmidt, 2015). 1 Similarly, when creditors threaten a firm with bankruptcy, an AOD can offer firm-specific bankruptcy advice and capitalize on his connections at banks and financial government agencies to negotiate favorable terms, thereby aiding the firm's emergence from bankruptcy (Arora, 2016). 2 When external threats create high information asymmetry between insiders and outsiders (Hoshi, Kashyap, & Scharfstein, 1990), firm executives are more likely to trust AODs and share sensitive, relevant, firm information with AODs-especially those with social ties to them-compared to their IODs (Adams & Ferreira, 2007).…”
Section: Advising and Liaising Under External Control Threatsmentioning
confidence: 99%
“…In firms facing takeovers, AODs sided with firm managers to obtain higher premium offers (Bange & Mazzeo, 2004;Schmidt, 2015). In distressed firms, AODs negotiate with banks to obtain favorable terms (Arora, 2016).…”
Section: Resource Dependence Theorymentioning
confidence: 99%
See 1 more Smart Citation